Enhancement of dielectric and ferroelectric properties in flexible polymer for energy storage applications. Issue 15 (15th October 2020) - Ishaq, Saira; Kanwal, Farah; Atiq, Shahid; Noreen, Sadia; Moussa, Mahmoud; Azhar, Umar; Losic, Dusan
Abstract: In the present paper, synthesis and characterizations of flexible dielectric and ferroelectric polymer films combining different ratios of graphene, barium titanate and polydimethylsiloxane are presented. Broad range of characterization techniques were carried out to confirm their, morphological, structural, chemical, thermal and mechanical (flexibility, stretching, bending and twisting) characteristics. Dielectric studies showed that a high dielectric constant of the nanocomposite was dependent on the ratio of graphene:bariumtitanate:polydimethylsiloxane, showing that ratio of 15:25:100 had a high dielectric constant at high frequency range and the ratio 15:30:100 at the low frequency range. At 2 Hz the ratio 15:30:100 showed a dielectric constant of 116.9 which decreased to 30.6 at 2 MHz, thus showing capacitive nature at full frequency range. Meanwhile dielectric loss was very low i.e., 1.3 at 20 Hz and 0.02 at 2 MHz and AC conductivity was 1.6 × 10 −7 S/m. Ferroelectric properties like energy density, energy loss and efficiency were calculated and compared. At an electric field of 0.92 kV/cm, remanant polarization and coercive field were 3.9 × 10 −4 μC/cm 2 and15.82 kV/cm, respectively. Energy density of 0.64 J/m 3, energy loss 0.358 J/m 3 and efficiency 64.2% were confirmed respectively. Results indicate that the nanocomposite films having desirable performances such as flexibility, thermal stability, high dielectric constant, high energy density are good candidates to be considered in energy storage and memory device applications.